The Influence of Leadership Style, Work Motivation, and Work Discipline on Employee Performance at PT PG Rajawali II Sindanglaut Unit - Faisal Mulyana; Edy Hartono (Journal Research of Social Science, Economics, and Management, 2026)
Employee performance is a crucial factor in determining organizational success, particularly in industries facing increasing competition and operational transformation. PT PG Rajawali II Sindanglaut Unit, a state-owned sugar manufacturing company undergoing revitalization, requires highly productive employees to achieve its organizational objectives. However, differences in leadership practices, employee motivation, and work discipline may influence performance outcomes. Therefore, this study aims to analyze the effects of leadership style, work motivation, and work discipline on employee performance, both partially and simultaneously. This research employed a quantitative associative approach involving 109 employees of PT PG Rajawali II Sindanglaut Unit. Data were collected through structured questionnaires using a Likert scale and analyzed using SPSS software. The analytical techniques included validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination test. The results revealed that leadership style had a positive but insignificant effect on employee performance. In contrast, work motivation and work discipline had positive and significant effects on employee performance, with work discipline emerging as the most dominant factor. Simultaneously, leadership style, work motivation, and work discipline significantly influenced employee performance. The model explained 41.8% of the variation in employee performance. In conclusion, improving employee motivation and strengthening work discipline are essential strategies for enhancing employee performance. Organizations should also foster adaptive leadership practices to support sustainable organizational effectiveness and competitiveness.